SAMS teach yourself Windows XP in 21 days - Mueller, John 1958- (Sams teach yourself in 21 days, 2002)
John guides the reader through the new and unfamiliar Windows interface, while introducing the new features. The book provides information in several formats, all integrated with theory, tutorials, procedures, tips and comprehensive.